Molybdenum carbide, composite, catalyst ink, method for producing molybdenum carbide, and method for producing composite
By controlling the crystal structure and composition of molybdenum carbide and combining precious metals or transition metal composites, the problem of insufficient performance and conductivity of molybdenum carbide catalysts in the prior art is solved, and efficient catalyst material preparation is achieved, suitable for water electrolytic catalysts, and Reduces the stringency of process conditions.
Patent Information
- Application Number
- CN202380038526.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-05
- Filing Date
- 2023-08-03
- Publication Date
- 2024-12-20
AI Technical Summary
The existing molybdenum carbide manufacturing methods are difficult to control the particle structure and composition, resulting in insufficient catalyst performance and electrical conductivity, and high-temperature gas phase reactions require strict conditions.
Molybdenum carbide with Mo2C crystal structure, the carbon content is more than 6% of the total mass of molybdenum carbide, and the graphite and diamond belts were detected by Raman spectroscopy. The specific surface area was determined by BET method to be 10-2000m2/g, and the dynamic light scattering method was calculated. The median particle size D50 is less than 1000 nm, the average crystalline size is less than 50 nm, and the composite of noble metal or transition metal is combined with a composite of α-crystal molybdenum trioxide and an inorganic compound as flux are used for firing.
Molybdenum carbide with the desired particle structure and composition is obtained, which improves the catalyst performance and conductivity, is suitable for water electrolytic catalysts, and has relatively mild process conditions and is easy to produce on a large scale.
Smart Images

Figure CN119173474A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to molybdenum carbide, a composite material, catalyst ink, a method for producing molybdenum carbide, and a method for producing the composite material.
[0002] This application claims priority based on Japanese Patent Application No. 2022-125418 filed in Japan on August 5, 2022, the contents of which are incorporated herein by reference. Background Art
[0003] In the process of aiming to solve environmental problems and energy resource problems, water electrolysis technology has attracted attention as a technology for generating hydrogen from water using electricity from renewable energy.
[0004] Molybdenum carbide (Mo 2 Molybdenum compounds represented by C) are expected to be inexpensive, abundant in resources, and have high catalytic activity.
[0005] As an electrode for hydrogen generation, for example, Patent Document 1 describes an electrode for hydrogen generation, which at least includes: a metal (A) that undergoes a Volmer reaction on the metal surface, and a metal (B) that undergoes a Heyrovsky reaction or a Tafel reaction on the metal surface. Patent Document 2 describes that the combination of metal (A) and metal (B) may be a combination of at least one metal selected from the group consisting of molybdenum carbide, molybdenum boride, molybdenum oxide, nickel molybdate, molybdenum sulfide, tungsten carbide, tungsten boride, and tungsten oxide and at least one metal selected from the group consisting of nickel and cobalt.
[0006] Various methods for producing molybdenum carbide have been proposed. For example, Patent Document 2 describes a method in which a compound of a heavy metal such as Mo in a gaseous state is heated to 900°C to 1400°C and mixed with a 200 m 2 / g or more of reactive carbon with a specific surface area of 1.5 to 2.5 g.
[0007] Prior art literature
[0008] Patent Literature
[0009] Patent Document 1: Japanese Patent Application Publication No. 2001-234380
[0010] Patent Document 2: Japanese Patent Publication No. 3-501721 Summary of the invention
[0011] Problems to be solved by the invention
[0012] However, it is difficult to control the particle structure and composition of molybdenum carbide in the method described in Patent Document 2. Therefore, there is room for improvement in the catalyst performance and conductivity of molybdenum carbide.
[0013] In addition, the method described in Patent Document 2 requires strict reaction conditions because it is a high-temperature gas phase reaction.
[0014] The present invention is completed in view of the above matters, and its subject is to provide molybdenum carbide having a desired particle structure and composition, a catalyst ink containing the molybdenum carbide, a complex of the molybdenum carbide and precious metal particles or transition metals or transition metal compounds, a catalyst ink containing the complex, a method for manufacturing molybdenum carbide, and a method for manufacturing the complex.
[0015] Means for solving problems
[0016] The present invention includes the following aspects.
[0017] (1) A molybdenum carbide having Mo 2 C crystal structure, and the carbon content is 6% or more relative to the total mass (100% by mass) of the molybdenum carbide.
[0018] (2) The molybdenum carbide as described in the above (1), wherein graphite ribbons G and diamond ribbons D derived from carbon are present as measured by Raman spectroscopy.
[0019] (3) The molybdenum carbide according to the above (2), wherein the ratio (G / D) of the carbon-derived graphite ribbon G to the diamond ribbon D is 0.75 or more.
[0020] (4) The molybdenum carbide according to any one of (1) to (3) above, wherein the specific surface area measured by the BET method is 10 to 2000 m 2 / g.
[0021] (5) The molybdenum carbide according to any one of (1) to (4) above, wherein the median particle size D is calculated by dynamic light scattering method. 50 Below 1000nm.
[0022] (6) The molybdenum carbide as described in any one of (1) to (5) above, wherein the average crystallite size determined from the peak at 2θ=39.4±0.5° of a pattern obtained by X-ray diffraction measurement is 50 nm or less.
[0023] (7) A catalyst ink comprising the molybdenum carbide according to any one of (1) to (6) above, and a solvent.
[0024] (8) A composite material comprising noble metal particles having an average particle size of 20 nm or less and the molybdenum carbide described in any one of (1) to (6) above.
[0025] (9) The composite material according to (8) above, wherein the noble metal particles are palladium particles.
[0026] (10) The composite material according to (9) above, wherein the palladium particles include an aggregate of palladium atoms having no crystal structure.
[0027] (11) A catalyst ink comprising the composite according to any one of (8) to (10) above, and a solvent.
[0028] (12) A composite material comprising at least one transition metal species selected from the group consisting of transition metals and transition metal compounds and the molybdenum carbide according to any one of (1) to (6) above.
[0029] (13) The composite material with molybdenum carbide as described in (12) above, wherein the transition metal species is at least one selected from the group consisting of nickel and nickel compounds.
[0030] (14) A catalyst ink comprising the composite according to (12) or (13) above, and a solvent.
[0031] (15) A method for producing molybdenum carbide, comprising: calcining molybdenum trioxide containing α crystals having an average crystallite size of 50 nm or less, and carbon in the presence of at least one inorganic compound selected from the group consisting of inorganic salts and inorganic hydroxides.
[0032] (16) The method for producing molybdenum carbide according to (15) above, wherein the inorganic compound is at least one selected from the group consisting of sodium compounds and potassium compounds.
[0033] (17) A method for producing a composite, comprising the steps of mixing molybdenum carbide with a noble metal solution,
[0034] The above molybdenum carbide has Mo 2 C crystal structure, and the carbon content is 6% or more relative to the total mass (100% by mass) of the molybdenum carbide.
[0035] (18) A method for producing a composite, comprising the step of mixing molybdenum carbide and a transition metal compound solution,
[0036] The above molybdenum carbide has Mo 2 C crystal structure, and the carbon content is 6% or more relative to the total mass (100% by mass) of the molybdenum carbide.
[0037] Effects of the Invention
[0038] According to the present invention, there can be provided a molybdenum carbide having a desired particle structure and composition, a catalyst ink containing the molybdenum carbide, a complex of the molybdenum carbide and precious metal particles or transition metals or transition metal compounds, a catalyst ink containing the complex, a method for manufacturing molybdenum carbide, and a method for manufacturing the complex. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] [ Figure 1 ] is a schematic diagram showing an example of an apparatus for producing molybdenum trioxide particles, which are the raw material of molybdenum disulfide particles of the composite of the embodiment.
[0040] [ Figure 2 ] is a graph showing the X-ray diffraction (XRD) curves of the particles obtained in Examples 1 to 3 superimposed on each other.
[0041] [ Figure 3 ] are transmission electron microscope (TEM, manufactured by JEOL Ltd., JEM-1400) images of the particles obtained in Examples 1 to 3.
[0042] [ Figure 4 ] is an observation image of the particles of Example 1 obtained by a high-resolution transmission electron microscope (HRTEM, manufactured by JEOL Ltd., JEM-ARM300F).
[0043] [ Figure 5 ] is a graph showing the X-ray diffraction (XRD) curves of each particle obtained in Examples 4 to 6 and Comparative Examples 1 and 4 superimposed.
[0044] [ Figure 6 ] is a transmission electron microscope (TEM, manufactured by JEOL Ltd., JEM-1400) image of each particle obtained in Examples 4 and 6.
[0045] [ Figure 7 ] is an observation image of the particles of Example 4 obtained by a high-resolution transmission electron microscope (HRTEM, manufactured by JEOL Ltd., JEM-ARM300F).
[0046] [ Figure 8 ] is a HAADF-STEM image of the particles of Example 4 (transmission electron image, manufactured by JEOL Ltd., JEM-ARM300F).
[0047] [ Fig. 9 ] is a SEI image of the particles of Example 4 (secondary electron image, manufactured by JEOL Ltd., JEM-ARM300F).
[0048] [ Fig.10] is a graph showing superimposed X-ray diffraction (XRD) curves of the particles obtained in Example 7 and Comparative Example 6.
[0049] [ Fig.11 ] is a high-resolution transmission electron microscope (HRTEM, manufactured by JEOL Ltd., JEM-ARM300F) image of the particles obtained in Example 7. DETAILED DESCRIPTION
[0050] <Molybdenum carbide>
[0051] The molybdenum carbide of this embodiment has a crystal structure of Mo 2 C crystal structure, and the carbon content is 6% or more relative to the total mass (100% by mass) of the molybdenum carbide.
[0052] In this embodiment, Mo 2 The presence of the crystal structure of C can be detected by using a diffraction pattern obtained by XRD analysis using molybdenum carbide as a sample. 2 The C crystal structure may be either an α crystal or a β crystal, but is preferably an α crystal.
[0053] The carbon content of the molybdenum carbide of the present embodiment is 6% or more, preferably 8% or more, more preferably 10% or more, and further preferably 15% or more, relative to the total mass (100% by mass) of the molybdenum carbide.
[0054] When the carbon content is at least the lower limit of the above range, the electrical conductivity of molybdenum carbide can be easily improved.
[0055] The upper limit of the carbon content of the molybdenum carbide of the present embodiment relative to the total mass (100 mass%) of the molybdenum carbide is not particularly limited, but is preferably 90% or less, more preferably 80% or less, and further preferably 60% or less.
[0056] When the carbon content is at most the upper limit value of the above range, the electrical conductivity and catalyst performance of molybdenum carbide can be easily improved.
[0057] In the present embodiment, regarding the composition analysis of molybdenum carbide, the molybdenum content can be determined by heated closed acid decomposition-ICP-AES (inductively coupled plasma atomic emission spectrometry), and the carbon content can be determined by CHN elemental analysis.
[0058] The molybdenum carbide of the present embodiment preferably contains graphite ribbons G and diamond ribbons D derived from carbon as measured by Raman spectroscopy. Specifically, the molybdenum carbide of the present embodiment preferably contains crystalline Mo 2 Mixed structure of C and carbon. Crystalline Mo 2 The existence state of C and carbon is not particularly limited, for example: 2The carbon exists on the surface of C, 2 The state of carbon domains dispersed in the matrix of C, etc.
[0059] In the present embodiment, the ratio (G / D) of the graphite ribbon G of molybdenum carbide to the diamond ribbon D is preferably 0.75 or more, more preferably 0.78 or more, and even more preferably 0.80 or more.
[0060] When G / D is at least the lower limit of the above range, defects originating from the diamond tape D are reduced, and the electrical conductivity and catalyst performance of molybdenum carbide are easily improved.
[0061] In the present embodiment, the upper limit of the G / D ratio is not particularly limited, but is preferably 2.0 or less, more preferably 1.5 or less, and further preferably 1.0 or less.
[0062] When the G / D ratio is at most the upper limit value of the above range, a synergistic effect with molybdenum carbide is likely to be exhibited, and catalyst performance is likely to be improved.
[0063] In this embodiment, the specific surface area of molybdenum carbide measured by the BET method is preferably 10 to 2000 m 2 / g, more preferably 20 to 1500 m 2 / g, more preferably 50 to 1500 m 2 / g.
[0064] If the specific surface area measured by the BET method is within the above-mentioned preferred range, for example, when molybdenum carbide is used as a catalyst, it is easy to increase the catalyst reaction sites, facilitate the movement of substances in the reaction system, and further effectively improve the catalyst efficiency.
[0065] The specific surface area is measured by using a specific surface area meter (e.g., Microtrac BEL, BELSORP-mini), and the surface area per 1 g of the sample measured by the BET method (Brunauer-Emmett-Teller method) based on the amount of nitrogen adsorption is calculated as the specific surface area (m 2 / g).
[0066] In this embodiment, the median particle size D of molybdenum carbide calculated by dynamic light scattering method is 50 It is preferably 1500 nm or less, more preferably 1000 nm or less, and further preferably 500 nm or less.
[0067] If the median particle size D 50 When the content is not more than the upper limit of the above preferred range, for example, when molybdenum carbide is used as a catalyst, the catalytic efficiency can be more effectively exhibited.
[0068] Median particle size D of molybdenum carbide according to the embodiment determined by dynamic light scattering 50 As an example, it may be greater than 20 nm, or greater than 40 nm.
[0069] The median particle size D of the molybdenum carbide as an embodiment obtained by the dynamic light scattering method is 50 An example of the numerical range of the above numerical value may be 20 nm or more and 1500 nm or less, 40 nm or more and 1000 nm or less, or 40 nm or more and 500 nm or less.
[0070] Regarding the median particle size D calculated by the dynamic light scattering method of the molybdenum carbide according to the embodiment 50 The particle size at which the volume cumulative % ratio becomes 50% can be determined from the particle size distribution measured in a wet method using a dynamic light scattering particle size distribution analyzer (for example, Nanotrac Wave II manufactured by MicrotracBEL).
[0071] In the present embodiment, the average crystallite size of molybdenum carbide determined from the peak at 2θ=39.4±0.5° of a pattern obtained by X-ray diffraction measurement is preferably 50 nm or less, more preferably 45 nm or less, and even more preferably 40 nm or less.
[0072] The above average crystallite size is considered to reflect the particle size and shape of the molybdenum carbide particles. When the crystallite size is smaller, there is a tendency for the number of catalyst reaction sites such as interfaces and defects to increase, which is preferred.
[0073] Regarding the lower limit of the average crystallite size of the above-mentioned molybdenum carbide determined from the peak of 2θ=39.4±0.5° in the pattern obtained by X-ray diffraction measurement, as an example, it can be greater than 1 nm, greater than 3 nm, greater than 4 nm, or greater than 5 nm.
[0074] The above-mentioned average crystallite size of the molybdenum carbide according to the embodiment can be specified by the following measuring method.
[0075] [Determination of crystallite size]
[0076] An X-ray diffraction device (e.g., SmartLab 9kW manufactured by Rigaku Co., Ltd.) is used, and a scintillation counter is used as a detector, and PDXL2 is used as the analytical software for measurement. The measurement method is the 2θ / θ method, and the average crystallite size is calculated using the Scherrer formula based on the half-height width of the peak appearing at 2θ=39.4±0.5°. Furthermore, as measurement conditions, the scanning speed (2θ) is 2.0° / min, the scanning range (2θ) is 10-70°, the spacing (2θ) is 0.02°, and the device standard width is set to none.
[0077] The molybdenum carbide of this embodiment has a crystal structure of Mo 2 C crystal structure, and the carbon content is 6% or more relative to the total mass (100% by mass) of the molybdenum carbide. Therefore, the molybdenum carbide of this embodiment has a high specific surface area, good conductivity and catalyst performance, and is particularly useful in the use of water electrolysis catalysts.
[0078] <Method for producing molybdenum carbide>
[0079] The method for producing molybdenum carbide of the present embodiment includes calcining molybdenum trioxide including α crystals having an average crystallite size of 50 nm or less and carbon in the presence of at least one inorganic compound selected from the group consisting of inorganic salts and inorganic hydroxides.
[0080] The at least one inorganic compound is preferably an alkali metal compound, more preferably at least one selected from the group consisting of sodium compounds and potassium compounds, and still more preferably at least one selected from the group consisting of KCl, NaCl and KOH.
[0081] The amount of the at least one inorganic compound is not particularly limited, but is preferably 5% to 1000% of the mass of molybdenum trioxide and carbon, more preferably 10% to 500%, and even more preferably 20% to 200%.
[0082] When the amount of the at least one inorganic compound is within the preferred range, molybdenum carbide having high conductivity and catalytic activity is easily formed.
[0083] In this embodiment, the at least one inorganic compound functions as a flux to promote the reaction between molybdenum trioxide and carbon. The flux method is characterized in that inorganic compounds can be synthesized at a relatively lower temperature than normal calcination, or the crystal structure and composition can be controlled.
[0084] In the production method of the present embodiment, the calcination temperature is not particularly limited, but is preferably 400 to 1500°C, more preferably 500 to 1000°C, and even more preferably 750 to 880°C.
[0085] When the calcination temperature is within the above preferred range, molybdenum carbide having high electrical conductivity and catalytic activity is easily formed.
[0086] In the production method of the present embodiment, the heating time is not particularly limited as long as it is a time for the reaction to proceed sufficiently, and may be 1 to 48 hours, 2 to 24 hours, or 4 to 12 hours.
[0087] The production method of the present embodiment may include the step of, after calcining molybdenum trioxide and carbon, washing the calcined product with water to remove the at least one inorganic compound.
[0088] In the production method of the present embodiment, the carbon is not particularly limited, and commercially available carbon particles such as carbon black and carbon nanotubes can be used.
[0089] In the production method of this embodiment, the median particle size D of the primary particles of the molybdenum trioxide powder obtained by dynamic light scattering is 50 It is preferably from 10 nm to 2000 nm, more preferably from 10 nm to 500 nm, and even more preferably from 10 nm to 200 nm.
[0090] If the median particle size D of the primary particles 50 When the molybdenum trioxide powder has a particle size within the above preferred range, the reactivity of the molybdenum trioxide powder with carbon is likely to be better. 50 For example, it is calculated from the volume-based cumulative particle size distribution measured using a dynamic light scattering particle size distribution analyzer.
[0091] In the present embodiment, the average particle size of the primary particles of the molybdenum trioxide powder refers to the average value of the primary particle sizes of 50 randomly selected primary particles when the molybdenum trioxide powder is photographed using a transmission electron microscope (TEM) or a scanning electron microscope (SEM), and the major axis (the Feret's diameter of the longest observed part) and the minor axis (the shorter Feret's diameter in a direction perpendicular to the Feret's diameter of the longest part) of the smallest unit particle (i.e., the primary particle) constituting the agglomerate on the two-dimensional image are measured, and the average value is used as the primary particle size.
[0092] In this embodiment, the total mass of the molybdenum trioxide powder is 2.3477 W / m2 and 2.322 W / m2 by X-ray fluorescence (XRF). 3 The content ratio of is preferably 99.5% by mass or more, more preferably 99.7% by mass or more, and further preferably 99.9% by mass or more, based on the total detected peak intensity.
[0093] If MoO 3 When the content ratio is within the above preferred range, high-purity molybdenum carbide with good storage stability can be easily obtained by subjecting the molybdenum trioxide powder to a carbonization reaction without worrying about the generation of carbides from impurities.
[0094] In the present embodiment, the specific surface area of the molybdenum trioxide powder is preferably 10 m 2 / g or more, more preferably 20m 2 / g or more, more preferably 30m 2 / g or more. In terms of facilitating the production of molybdenum trioxide powder, 100 m2 / g or less, also 90m 2 / g or less, also 80m 2 / g or less.
[0095] In this embodiment, the average crystallite size of α crystals contained in the crystal structure of molybdenum trioxide is less than 50 nm, preferably greater than 5 nm and less than 50 nm, more preferably greater than 5 nm and less than 45 nm, further preferably greater than 10 nm and less than 40 nm, and particularly preferably greater than 10 nm and less than 35 nm.
[0096] When the average crystallite size of the α crystals is within the above range, the reactivity of the molybdenum trioxide powder with carbon tends to be further improved.
[0097] In the present embodiment, the crystal structure of molybdenum trioxide may further include β crystals having an average crystallite size of 50 nm or less. If the crystal structure of molybdenum trioxide includes α crystals and β crystals, the reactivity of molybdenum trioxide powder with carbon is likely to be further improved.
[0098] In the present embodiment, the average crystallite size of β crystals contained in the crystal structure of molybdenum trioxide is preferably greater than 5 nm and less than 50 nm, more preferably greater than 5 nm and less than 45 nm, further preferably greater than 10 nm and less than 40 nm, and particularly preferably greater than 10 nm and less than 30 nm.
[0099] When the average crystallite size of the β crystals is within the above preferred range, the reactivity of the molybdenum trioxide powder with carbon tends to be further improved.
[0100] In this embodiment, the α crystal structure of molybdenum trioxide can be confirmed by the following method: in the pattern obtained by powder X-ray diffraction (XRD) using Cu-Kα rays as an X-ray source, there is MoO 3 The peak of the (021) plane of the α crystal (2θ: 27.32°, No. 166363 (Inorganic Crystal Structure Database, ICSD)) can be confirmed by the following method: In the pattern obtained by powder X-ray diffraction (XRD) using Cu-Kα rays as the X-ray source, there is a peak attributed to MoO 3 The peak of the (011) plane of the β crystal (2θ: around 23.01°, No.86426 (Inorganic Crystal Structure Database, ICSD)).
[0101] In this embodiment, the molybdenum trioxide powder is attributed to MoO in the pattern obtained by powder X-ray diffraction (XRD) using Cu-Kα rays as an X-ray source. 3 The peak intensity of the (011) plane of the β crystal is relatively large relative to that of MoO3 The ratio of the peak intensity of the (021) plane of the α crystal (β(011) / α(021)) is preferably 0.1 or more, more preferably 0.2 or more, and further preferably 0.4 or more.
[0102] In the present embodiment, the above ratio (β(011) / α(021)) of the molybdenum trioxide particles is preferably 10.0 or less.
[0103] Attribution to MoO 3 The peak intensity of the (011) plane of the β crystal and the peak intensity of MoO 3 The peak intensity of the (021) plane of the α crystal is measured by reading the maximum intensity of the peak, and the above ratio (β(011) / α(021)) is calculated.
[0104] In the present embodiment, the above ratio (β(011) / α(021)) of the molybdenum trioxide powder is preferably 0.1 to 10.0, more preferably 0.2 to 10.0, and particularly preferably 0.4 to 10.0.
[0105] In the present embodiment, the content of α crystals in the molybdenum trioxide powder is not particularly limited, and may be 20% or more, 50% or more, 70% or more, 80% or more, or 100%.
[0106] at MoO 3 In the mixture of α crystal and β crystal, MoO 3 The content of α crystals can be obtained by using the RIR (reference intensity ratio) method based on the obtained graph data. 3 The RIR value K of α crystal A and MoO 3 The integrated intensity I of the (021) plane of the α crystal (2θ: 27.32°, No.166363 (Inorganic Crystal Structure Database, ICSD)) A , and MoO 3 The RIR value K of the β crystal B and attributable to MoO 3 The integrated intensity I of the (011) plane of the β crystal (2θ: around 23.01°, No.86426 (Inorganic Crystal Structure Database, ICSD)) B , MoO is obtained by the following formula (2): 3 The content rate (%) of α crystal.
[0107] MoO 3 The content of α crystals (%) = (I A / K A ) / ((I A / K A )+(IB / K B ))×100···(2)
[0108] Here, the RIR values may be values described in the ICSD database, and comprehensive powder X-ray analysis software (PDXL2, manufactured by Rigaku Corporation) may be used for analysis.
[0109] (Method for producing molybdenum trioxide powder)
[0110] The molybdenum trioxide powder can be produced by gasifying a molybdenum oxide precursor compound to form molybdenum trioxide vapor, and cooling the molybdenum trioxide vapor.
[0111] The method for manufacturing the above-mentioned molybdenum trioxide powder includes calcining a raw material mixture containing a molybdenum oxide precursor compound and a metal compound other than the above-mentioned molybdenum oxide precursor compound, gasifying the above-mentioned molybdenum oxide precursor compound to form molybdenum trioxide vapor, and the ratio of the above-mentioned metal compound to 100% by mass of the above-mentioned raw material mixture is preferably less than 70% by mass when converted to oxide.
[0112] The method for producing the molybdenum trioxide powder can be used Figure 1 The production device 1 shown is suitably embodied.
[0113] Figure 1 1 is a schematic diagram of an example of an apparatus for producing the above-mentioned molybdenum trioxide powder. The manufacturing apparatus 1 comprises: a sintering furnace 2, which sinters a molybdenum oxide precursor compound or the above-mentioned raw material mixture to gasify the above-mentioned molybdenum oxide precursor compound; a cross (cross) type cooling pipe 3, which is connected to the above-mentioned sintering furnace 2, and powderizes the molybdenum trioxide vapor gasified by the above-mentioned sintering; and a recovery machine 4, which is a recovery mechanism for recovering the molybdenum trioxide powder powderized in the above-mentioned cooling pipe 3. At this time, the above-mentioned sintering furnace 2 and the cooling pipe 3 are connected via an exhaust port 5. In addition, the above-mentioned cooling pipe 3 is respectively provided with an opening adjustment damper 6 at the left end at the external gas intake port (not shown), and an observation window 7 is provided at the upper end. An exhaust device 8 as a first air supply mechanism is connected to the recovery machine 4. The exhaust device 8 is used to exhaust air, and the recovery machine 4 and the cooling pipe 3 are sucked, and the external air is blown from the opening adjustment damper 6 of the cooling pipe 3 to the cooling pipe 3. That is, the exhaust device 8 exerts a suction function to passively generate air supply in the cooling pipe 3. Furthermore, the production apparatus 1 may include an external cooling device 9, whereby the cooling conditions of the molybdenum trioxide vapor generated from the calcining furnace 2 can be arbitrarily controlled.
[0114] Air is sucked in from the external air intake port by opening the damper 6, so that the molybdenum trioxide vapor gasified in the sintering furnace 2 is cooled in the air environment to form molybdenum trioxide powder. Thus, the above ratio (I / II) can be made greater than 1.1, and MoO can be easily obtained in the molybdenum trioxide powder. 3 When using liquid nitrogen to cool molybdenum trioxide vapor, cooling the molybdenum trioxide vapor in a nitrogen environment with a low oxygen concentration tends to increase the oxygen defect density and reduce the above ratio (I / II).
[0115] The molybdenum oxide precursor compound is not particularly limited as long as it is a precursor compound for forming a molybdenum trioxide powder composed of an aggregate of primary particles having a β crystal structure containing molybdenum trioxide.
[0116] The molybdenum oxide precursor compound is not particularly limited as long as it is a compound that forms molybdenum trioxide vapor upon calcination, and examples thereof include metal molybdenum, molybdenum trioxide, molybdenum dioxide, molybdenum sulfide, ammonium molybdate, phosphomolybdic acid (H 3 PMo 12 O 40 ), silicomolybdic acid (H 4 SiMo 12 O 40 ), aluminum molybdate, silicon molybdate, magnesium molybdate (MgMo n O 3n+1 (n=1~3))、Sodium molybdate (Na 2 Mo n O 3n+1 (n = 1 to 3)), titanium molybdate, iron molybdate, potassium molybdate (K 2 Mo n O 3n+1 (n = 1 to 3)), zinc molybdate, boron molybdate, lithium molybdate (Li 2 Mo n O 3n+1 (n=1-3)), cobalt molybdate, nickel molybdate, manganese molybdate, chromium molybdate, cesium molybdate, barium molybdate, strontium molybdate, yttrium molybdate, zirconium molybdate, copper molybdate, etc. These molybdenum oxide precursor compounds can be used alone or in combination of two or more. The form of the molybdenum oxide precursor compound is not particularly limited, for example, it can be a powder such as molybdenum trioxide, or a liquid such as an aqueous solution of ammonium molybdate. It is preferably a powder with good handling properties and energy efficiency.
[0117] As the molybdenum oxide precursor compound, it is preferred to use commercially available α-crystal molybdenum trioxide. In addition, when ammonium molybdate is used as the molybdenum oxide precursor compound, it is converted into thermodynamically stable molybdenum trioxide by calcination, so the vaporized molybdenum oxide precursor compound becomes the above-mentioned molybdenum trioxide.
[0118] Among these molybdenum oxide precursor compounds, it is preferred that molybdenum trioxide is contained from the viewpoint of facilitating control of the purity, average particle size of primary particles, and crystal structure of the obtained molybdenum trioxide powder.
[0119] Molybdenum trioxide vapor can also be generated by calcining a raw material mixture containing a molybdenum oxide precursor compound and a metal compound other than the molybdenum oxide precursor compound.
[0120] The metal compound other than the above-mentioned molybdenum oxide precursor compound is not particularly limited, and examples thereof include aluminum compounds, silicon compounds, titanium compounds, magnesium compounds, sodium compounds, potassium compounds, zirconium compounds, yttrium compounds, zinc compounds, copper compounds, iron compounds, etc. Among these, aluminum compounds, silicon compounds, titanium compounds, and magnesium compounds are preferably used.
[0121] The molybdenum oxide precursor compound and the metal compound other than the above-mentioned molybdenum oxide precursor compound may generate an intermediate. Even in this case, the intermediate is decomposed by calcination to vaporize molybdenum trioxide in a thermodynamically stable form.
[0122] As the metal compound other than the above-mentioned molybdenum oxide precursor compound, among these, aluminum compounds are preferably used in order to prevent damage to the sintering furnace. In order to improve the purity of the molybdenum trioxide powder, metal compounds other than the above-mentioned molybdenum oxide precursor compound may not be used.
[0123] Examples of the aluminum compound include aluminum chloride, aluminum sulfate, basic aluminum acetate, aluminum hydroxide, boehmite, pseudo-boehmite, transition alumina (γ-alumina, δ-alumina, θ-alumina, etc.), α-alumina, and mixed alumina having two or more crystal phases.
[0124] When a raw material mixture containing a molybdenum oxide precursor compound and a metal compound other than the molybdenum oxide precursor compound is calcined, the content ratio of the molybdenum oxide precursor compound relative to 100 mass % of the raw material mixture is preferably 40 to 100 mass %, may be 45 to 100 mass %, or may be 50 to 100 mass %.
[0125] The calcination temperature also varies depending on the molybdenum oxide precursor compound, metal compound, and desired molybdenum trioxide powder used, but is generally preferably set to a temperature at which the intermediate can be decomposed. For example, when a molybdenum compound is used as the molybdenum oxide precursor compound and an aluminum compound is used as the metal compound, aluminum molybdate can be formed as an intermediate, so the calcination temperature is preferably 500 to 1500° C., more preferably 600 to 1550° C., and further preferably 700 to 1600° C.
[0126] The firing time is not particularly limited, and may be, for example, 1 minute to 30 hours, 10 minutes to 25 hours, or 100 minutes to 20 hours.
[0127] The heating rate also varies depending on the properties of the molybdenum oxide precursor compound used, the above-mentioned metal compound, and the required molybdenum trioxide powder, but from the perspective of manufacturing efficiency, it is preferably above 0.1°C / min and below 100°C / min, more preferably above 1°C / min and below 50°C / min, and further preferably above 2°C / min and below 10°C / min.
[0128] The internal pressure in the calcining furnace is not particularly limited, and may be either positive pressure or reduced pressure, but from the viewpoint of appropriately discharging the molybdenum oxide precursor compound from the calcining furnace to the cooling pipe, calcining is preferably carried out under reduced pressure. As a specific degree of reduced pressure, preferably -5000Pa to -10Pa, more preferably -2000Pa to -20Pa, and further preferably -1000Pa to -50Pa. If the degree of reduced pressure is above -5000Pa, high air tightness and mechanical strength of the calcining furnace will not be excessively required, and the manufacturing cost can be reduced, so it is preferred. On the other hand, if the degree of reduced pressure is below -10Pa, it is possible to prevent the molybdenum oxide precursor compound from clogging at the discharge port of the calcining furnace, so it is preferred.
[0129] Furthermore, when gas is blown into the firing furnace during the firing process, the temperature of the blown gas is preferably 5 to 500°C, more preferably 10 to 100°C.
[0130] Furthermore, the blowing rate of the gas is preferably 1 L / min to 500 L / min, and more preferably 10 L / min to 200 L / min, with respect to a firing furnace having an effective volume of 100 L.
[0131] The temperature of the vaporized molybdenum trioxide vapor also varies depending on the type of molybdenum oxide precursor compound used, but is preferably 200 to 2000° C., and more preferably 400 to 1500° C. Furthermore, if the temperature of the vaporized molybdenum trioxide vapor is 2000° C. or less, it is usually easy to be powdered by blowing external air (0 to 100° C.) in the cooling pipe.
[0132] The discharge rate of the molybdenum trioxide vapor discharged from the calcining furnace can be controlled by the amount of the molybdenum oxide precursor compound used, the amount of the metal compound, the temperature of the calcining furnace, the gas blown into the calcining furnace, and the diameter of the exhaust port of the calcining furnace. The discharge rate of the molybdenum trioxide vapor from the calcining furnace to the cooling pipe varies depending on the cooling capacity of the cooling pipe, but is preferably 0.001 g / min or more and 100 g / min or less, and more preferably 0.1 g / min or more and 50 g / min or less.
[0133] The content of molybdenum trioxide vapor contained in the gas exhausted from the calcining furnace is preferably 0.01 g / min or more and 1000 mg / L or less, and more preferably 1 g / min or more and 500 mg / L.
[0134] Next, the molybdenum trioxide vapor is cooled to be powdered.
[0135] The cooling of the molybdenum trioxide vapor is performed by setting the cooling pipe to a low temperature. At this time, as cooling means, there can be listed: cooling by blowing gas into the cooling pipe as described above, cooling by a cooling mechanism possessed by the cooling pipe, cooling by an external cooling device, etc.
[0136] The cooling of molybdenum trioxide vapor is preferably carried out in an air environment. By cooling molybdenum trioxide vapor in an air environment to prepare molybdenum trioxide powder, the above ratio (I / II) can be made greater than 1.1, and MoO 3 The β crystal structure.
[0137] The cooling temperature (temperature of the cooling pipe) is not particularly limited, but is preferably -100 to 600°C, more preferably -50 to 400°C.
[0138] The cooling rate of the molybdenum trioxide vapor is not particularly limited, but is preferably 100°C / s to 100,000°C / s, and more preferably 1,000°C / s to 50,000°C / s. In addition, the faster the cooling rate of the molybdenum trioxide vapor, the more likely it is that a molybdenum trioxide powder with a smaller particle size and a larger specific surface area can be obtained.
[0139] When the cooling means is cooling by blowing gas into the cooling pipe, the temperature of the blown gas is preferably -100 to 300°C, more preferably -50 to 100°C.
[0140] In addition, the blowing speed of the gas is preferably 0.1 m 3 / min or more and 20m 3 / min or less, more preferably 1m 3 / min or more and 10m 3 / min or less. If the gas blowing speed is 0.1m 3 / min or more, a higher cooling rate can be achieved, which can prevent the cooling pipe from being blocked, so it is preferred. On the other hand, if the gas blowing speed is 20m 3 / min or less, there is no need for an expensive first air supply mechanism (exhaust fan, etc.), which can reduce the manufacturing cost and is therefore preferred.
[0141] The powder obtained by cooling the molybdenum trioxide vapor is transported to a recovery machine for recovery.
[0142] In the method for producing the molybdenum trioxide powder, the powder obtained by cooling the molybdenum trioxide vapor may be calcined again at a temperature of 100 to 320°C.
[0143] That is, the molybdenum trioxide powder obtained by the above-mentioned method for manufacturing molybdenum trioxide powder can be calcined again at a temperature of 100 to 320°C. The calcination temperature for the re-calcination can be 120 to 280°C, or 140 to 240°C. The calcination time for the re-calcination can be, for example, 1 min to 4 h, 10 min to 5 h, or 100 min to 6 h. However, by re-calcining, part of the β crystal structure of molybdenum trioxide disappears. If calcined at a temperature above 350°C for 4 hours, the β crystal structure in the molybdenum trioxide powder disappears, the above ratio (β(011) / α(021)) becomes 0, and the reactivity with carbon is impaired.
[0144] According to the method for producing molybdenum carbide of the present embodiment, molybdenum carbide having a desired particle structure and composition can be obtained. In addition, according to the method for producing molybdenum carbide of the present embodiment, there are the following advantages: mass production is possible, no equipment with the risk of high pressure is required, and no post-processing process is required.
[0145] <First Catalyst Ink>
[0146] The catalyst ink of the present embodiment (hereinafter also referred to as “first catalyst ink”) contains the molybdenum carbide of the above-mentioned embodiment and a solvent.
[0147] The solvent is not particularly limited, and examples thereof include alcohol solvents such as methanol and ethanol, and mixed solvents of an alcohol solvent and water. Among them, methanol and ethanol are preferred as the solvent.
[0148] In the present embodiment, the solvent may be only one kind or two or more kinds.
[0149] The first catalyst ink of the present embodiment may further contain a conductive material.
[0150] Examples of the conductive material include carbon and metals having high conductivity.
[0151] The conductive material contained in the first catalyst ink may be only one kind or two or more kinds.
[0152] Examples of the conductive material include carbon black such as acetylene black, Cabot carbon black, and Ketjen black, graphite, carbon fiber, and metal powder. Ketjen black has a high specific surface area and conductivity, and is also excellent in suppressing the aggregation of molybdenum carbide.
[0153] Examples of the metal of the conductive material include gold, silver, copper, palladium, aluminum, rhodium, molybdenum, tungsten, iron, nickel, cobalt, and indium.
[0154] The first catalyst ink of the present embodiment may contain only one type of metal as a conductive material, or may contain two or more types of metal.
[0155] The first catalyst ink of the present embodiment may contain carbon instead of metal as the conductive material, may contain metal instead of carbon, or may contain both metal and carbon.
[0156] The first catalyst ink of the present embodiment can be applied to, for example, a working electrode substrate to form a catalyst layer.
[0157] The first catalyst ink of the present embodiment may further contain a polymer electrolyte.
[0158] As the polymer electrolyte, a polymer electrolyte generally used in the formation of the catalyst layer can be used. Specifically, examples include: a perfluorocarbon polymer having a sulfonic acid group (e.g., Nafion (registered trademark)), a hydrocarbon polymer compound having a sulfonic acid group, a polymer compound doped with an inorganic acid such as phosphoric acid, an organic / inorganic hybrid polymer partially substituted with a proton conductive functional group, and a proton conductor in which a phosphoric acid solution or a sulfuric acid solution is impregnated in a polymer matrix.
[0159] <Composite of noble metal particles and molybdenum carbide>
[0160] The composite material of the present embodiment (hereinafter also referred to as “first composite material”) is a composite material of noble metal particles having an average particle size of 20 nm or less and the molybdenum carbide of the above-mentioned embodiment.
[0161] (Precious Metal Particles)
[0162] In the present embodiment, the noble metal particles are not particularly limited, but are preferably gold, silver, platinum, palladium, rhodium, or iridium, and more preferably palladium.
[0163] In the present embodiment, the number of the noble metal particles may be only one, or two or more.
[0164] When the noble metal is palladium, the palladium particles contained in the first composite of the embodiment are granular structures containing palladium, and are composited with the molybdenum carbide particles to form a composite of palladium and molybdenum carbide.
[0165] The shape of the palladium particles is not particularly limited, and examples thereof include spherical shapes, hemispherical shapes, and the like.
[0166] The form in which the palladium particles of the first composite of the embodiment are contained is not particularly limited, but the palladium particles may be present on the surface of the molybdenum carbide particles or may be attached to the surface of the molybdenum carbide particles.
[0167] The number of palladium particles present per surface area of 100 nm×100 nm on the surface of the molybdenum carbide particles may be, for example, 5 to 5000, or 10 to 1000.
[0168] The average particle size of the palladium particles may be 20 nm or less, 15 nm or less, or 10 nm or less.
[0169] As a lower limit of the average particle size of the palladium particles, for example, it may be 0.5 nm or more, 0.7 nm or more, or 1 nm or more.
[0170] An example of the numerical range of the numerical value of the average particle size of the palladium particles may be 0.5 nm to 20 nm, 0.7 nm to 15 nm, or 1 nm to 10 nm.
[0171] Regarding the average particle size of the palladium particles, the first composite of the present embodiment was photographed using a transmission electron microscope (TEM), and the maximum length of the distance between two points on the contour line of 50 randomly selected palladium particles confirmed on the two-dimensional image was measured, and the average value was used.
[0172] The palladium particles are aggregates of palladium (Pd) atoms and are palladium particles containing palladium. The palladium contained in the composite of the embodiment is not particularly limited in its form, and for example, the palladium may be contained in the palladium particles as a palladium compound.
[0173] In the present embodiment, the palladium particles preferably have a crystal structure that does not show palladium metal crystals in a diffraction pattern of XRD analysis. In this case, the first composite of the present embodiment exhibits excellent catalytic performance.
[0174] In this embodiment, the palladium particles may include amorphous palladium. The palladium particles may include palladium in a form other than a molybdenum substituted for a portion of the crystal structure of molybdenum disulfide. The palladium particles may include zero-valent palladium. The palladium particles may include palladium having a crystal structure without palladium metal crystals.
[0175] Regarding the content ratio of the palladium in the above-mentioned contained form, the above-mentioned palladium particles may contain 50% or more of amorphous palladium on a molar basis relative to the palladium contained in the palladium particles. The above-mentioned palladium particles may contain 50% or more of palladium in a form that does not replace a portion of the molybdenum in the crystal structure of molybdenum disulfide on a molar basis relative to the palladium contained in the palladium particles. The above-mentioned palladium particles may contain 50% or more of zero-valent palladium on a molar basis relative to the palladium contained in the palladium particles. The above-mentioned palladium particles may contain 50% or more of palladium in a crystal structure (closest packing structure) that does not have a palladium metal crystal on a molar basis relative to the palladium contained in the palladium particles.
[0176] The first composite of the present embodiment may include amorphous palladium. The first composite of the embodiment may include palladium in a form other than molybdenum that replaces a portion of the crystal structure of molybdenum carbide. The first composite of the embodiment may include palladium having a valence of 0. The first composite of the embodiment may include palladium having a crystal structure that does not have a palladium metal crystal.
[0177] Regarding the palladium content ratio of the above-mentioned embodiment, the first composite of the embodiment may include 50% or more of amorphous palladium on a molar basis relative to the palladium contained in the first composite. The first composite of the embodiment may include 50% or more of palladium on a molar basis relative to the palladium contained in the first composite in a form that is not a part of the molybdenum that replaces the crystal structure of molybdenum carbide. The first composite of the embodiment may include 50% or more of palladium with a valence of 0 relative to the palladium contained in the composite on a molar basis. The first composite of the embodiment may include 50% or more of palladium with a crystal structure that does not have a palladium metal crystal relative to the palladium contained in the first composite on a molar basis.
[0178] The palladium in the first composite of the embodiment may form a palladium cluster. Alternatively, the palladium in the palladium particles may form a palladium cluster.
[0179] The presence of the crystal structure containing palladium can be detected by using the first composite material of the embodiment as a sample and obtaining a diffraction pattern through XRD analysis.
[0180] According to the first composite of the embodiment described above, excellent catalytic performance can be exhibited by forming a composite of the molybdenum carbide and metal particles (preferably palladium particles).
[0181] In addition, it is considered that the noble metal in the noble metal particles can exhibit more excellent catalyst performance by being present in molybdenum carbide preferably in the form of an aggregate of noble metal atoms instead of constituting a crystal structure of noble metal crystals.
[0182] The first composite material of the embodiment can be used as a catalyst, and in particular, can be suitably used as a hydrogen generation catalyst applied to water electrolysis and the like.
[0183] Furthermore, the first composite according to the embodiment can be suitably used as an electrode material used as a constituent material of an electrode catalyst layer.
[0184] <Method for producing the first composite>
[0185] The method for producing the first composite of the embodiment is not particularly limited, and typically includes a step of mixing the molybdenum carbide and a noble metal solution, and more preferably includes a step of mixing the molybdenum carbide and a palladium solution.
[0186] In the present embodiment, the number of the noble metal solutions may be only one, or may be two or more.
[0187] The palladium solution can be obtained by dissolving any palladium source in a solvent. As the palladium source, any palladium compound such as palladium acetate, palladium nitrate, palladium nitrite, palladium sulfate, palladium carbonate, palladium chloride, palladium hydroxide, and palladium oxide can be mentioned as long as the palladium solution can be produced.
[0188] In the present embodiment, the palladium solution may be only one kind or two or more kinds.
[0189] The solvent may be any solvent as long as it can dissolve the palladium source, and examples thereof include alcohols such as methanol, benzene, dichloromethane, acetone, and chloroform.
[0190] In the present embodiment, the solvent may be only one kind or two or more kinds.
[0191] The mixing method is not particularly limited, and preferably the palladium solution is mixed with the dispersion of molybdenum carbide.
[0192] The dispersion of molybdenum carbide can be obtained by mixing the solvent exemplified in the above palladium solution with molybdenum carbide.
[0193] A composite of the molybdenum carbide and the palladium particles may be formed by mixing a palladium solution with platinum carbide to obtain a mixture, and contacting the platinum carbide with the palladium solution.
[0194] From the viewpoint of preventing agglomeration of molybdenum carbide, for example, it is preferable to stir the mixture of the palladium solution and the molybdenum carbide. The stirring speed can be, for example, 50 to 1000 rpm.
[0195] The concentration of palladium in the palladium solution may be, for example, 0.00001 to 0.1 mol / L, or 0.0001 to 0.01 mol / L.
[0196] The temperature of the mixture of molybdenum carbide and the palladium solution may be such that the first composite is formed, and may be, for example, 10 to 100°C, or 20 to 80°C.
[0197] The retention time of the mixture of molybdenum carbide and the palladium solution may be any time sufficient to form the first composite, and may be, for example, 10 minutes to 48 hours, or 30 minutes to 12 hours.
[0198] In the method for manufacturing the first composite of the embodiment, in order to promote the photoreduction of palladium, the mixture of molybdenum carbide and palladium solution can be irradiated with light. Regarding the light irradiation, the amount of light and the wavelength can be appropriately selected in a manner to the extent that the palladium undergoes photoreduction. The light irradiation can be implemented by setting a light source and controlling the degree of light, or it can be irradiated with light of a general indoor environment (illuminated by fluorescent lamps, LEDs, etc.), or irradiated with natural light, etc.
[0199] In the method for producing the first composite of the embodiment, the first composite can be produced even without heat treatment. For example, the obtained first composite or the mixture of the palladium solution and the molybdenum carbide is preferably not heated at a temperature of 200° C. or higher, more preferably not heated at a temperature of more than 100° C., and even more preferably not heated at a temperature of more than 80° C.
[0200] After the composite is formed from the mixture, the composite can be separated by centrifugation, drying, or the like, thereby easily recovering the first composite of the embodiment.
[0201] <Hydrogen Generation Catalyst>
[0202] The first composite of the above-mentioned embodiment can be suitably used as a catalyst in a hydrogen generation reaction (HER) (sometimes referred to as a "hydrogen generation catalyst" in this specification). In addition, the first composite of the embodiment can also be used as a hydrogen generation catalyst by being used in combination with a conductive material. That is, as a preferred hydrogen generation catalyst, for example, a hydrogen generation catalyst containing the first composite of the embodiment can be cited, and the above-mentioned hydrogen generation catalyst can further contain a conductive material in addition to the first composite of the embodiment. The catalytic activity of the hydrogen generation catalyst containing the first composite of the embodiment and the conductive material in the hydrogen generation reaction (HER) becomes higher.
[0203] The conductive material mentioned above may be a known conductive material.
[0204] Examples of the conductive material include carbon and metals having high conductivity.
[0205] The conductive material contained in the hydrogen generation catalyst may be only one kind or two or more kinds.
[0206] Examples of the conductive material include carbon black such as acetylene black, Cabot black, and Ketjen black, graphite, carbon fiber, metal powder, etc. Ketjen black has a high specific surface area and conductivity, and is also excellent in that it can suppress aggregation of molybdenum carbide.
[0207] Examples of the metal of the conductive material include gold, silver, copper, aluminum, rhodium, molybdenum, tungsten, iron, nickel, cobalt, and indium.
[0208] The metal serving as the conductive material is different from the noble metal of the first composite of the embodiment, and is merely mixed with the first composite of the embodiment in the hydrogen generation catalyst.
[0209] The metal as the conductive material contained in the hydrogen generation catalyst may be only one kind or two or more kinds.
[0210] The hydrogen generation catalyst may contain carbon instead of metal, may contain metal instead of carbon, or may contain both metal and carbon, for example, as a conductive material.
[0211] In the hydrogen generation catalyst, the content of the conductive material is preferably 0.1 to 50% by mass, and more preferably 0.5 to 40% by mass, relative to the content of the first composite of the embodiment.
[0212] In the hydrogen generation catalyst, the total content of the first composite of the embodiment and the above-mentioned conductive material relative to the total mass (100 mass %) of the hydrogen generation catalyst is preferably 80 mass % or more, more preferably 90 mass % or more, and further preferably 95 mass % or more, for example, 97 mass % or more, and any one of 99 mass % or more, or 100 mass %. By the above ratio being above the above lower limit, the catalytic activity of the hydrogen generation catalyst in the hydrogen generation reaction (HER) becomes higher. The above ratio can be as long as it is less than 100 mass %.
[0213] <Second Catalyst Ink>
[0214] The first composite material is suitable as a component contained in catalyst ink.
[0215] The catalyst ink of the embodiment (hereinafter also referred to as “second catalyst ink”) contains the first composite of the embodiment and a solvent.
[0216] The second catalyst ink of the embodiment may contain the first composite of the embodiment, a polymer electrolyte, and a solvent.
[0217] The second catalyst ink of the present embodiment may further contain a conductive material. Examples of the conductive material include the conductive materials exemplified above.
[0218] The second catalyst ink can be applied to, for example, a working electrode substrate to form a catalyst layer.
[0219] As the polymer electrolyte, a polymer electrolyte generally used in the catalyst layer can be used. Specifically, examples include: perfluorocarbon polymers having sulfonic acid groups (e.g., Nafion (registered trademark)), hydrocarbon polymer compounds having sulfonic acid groups, polymer compounds doped with inorganic acids such as phosphoric acid, organic / inorganic hybrid polymers partially substituted with proton conductive functional groups, and proton conductors in which phosphoric acid solutions or sulfuric acid solutions are impregnated in polymer matrices.
[0220] As the solvent, there can be cited a solvent that can disperse the first composite of the embodiment and can be applied to the working electrode substrate to form a catalyst layer. As the above-mentioned solvent, preferably, it contains alcohols such as 1-propanol, 2-propanol, 1-butanol, 2-butanol, 1-pentanol, 2-pentanol, 1-hexanol, 2-hexanol, 1-heptanol, and 2-heptanol.
[0221] <Complex of transition metal species and molybdenum carbide>
[0222] The composite material of the present embodiment (hereinafter also referred to as “second composite material”) is a composite material of at least one transition metal species selected from the group consisting of transition metals and transition metal compounds and the above-mentioned molybdenum carbide.
[0223] (Transition metals, transition metal compounds)
[0224] In the present embodiment, the transition metal is not particularly limited, but is preferably nickel, iron, cobalt, chromium, vanadium, manganese, copper, zinc, ruthenium, or iridium, and more preferably nickel, iron, cobalt, or manganese.
[0225] In the present embodiment, the transition metal compound is not particularly limited, and examples thereof include transition metal hydroxides, transition metal oxides, and the like. Among them, the transition metal compound is preferably a nickel compound, and more preferably Ni(OH) 2 , NiO. In addition, the transition metal compound may be a compound containing two or more transition metals, for example, NiFeO x wait.
[0226] In the present embodiment, the transition metal species may be only one species or two or more species.
[0227] The shape of the primary particles in the two-dimensional image when the nickel compound is taken by a transmission electron microscope (TEM) can be particle-shaped, spherical, plate-shaped (sheet-shaped), needle-shaped, rope-shaped, or ribbon-shaped, or these shapes can be combined. In the present embodiment, the shape of the primary particles in the two-dimensional image when the nickel compound is taken by TEM is preferably sheet-shaped.
[0228] According to the second composite of the embodiment, the molybdenum carbide and the transition metal species (preferably a nickel compound) are composited to exhibit excellent catalytic performance.
[0229] The second composite of the embodiment can be used as a catalyst, and in particular, can be suitably used as an oxygen generation catalyst applied to water electrolysis and the like.
[0230] Furthermore, the second composite according to the embodiment can be suitably used as an electrode material used as a constituent material of an electrode catalyst layer.
[0231] <Method for producing the second composite>
[0232] The method for producing the second composite of the embodiment is not particularly limited, and typically includes a step of mixing the above-mentioned molybdenum carbide and a solution of a transition metal source.
[0233] As the transition metal source, for example, there can be mentioned: acetates of transition metals, nitrates of transition metals, nitrites of transition metals, sulfates of transition metals, carbonates of transition metals, chlorides of transition metals, hydroxides of transition metals, oxides of transition metals, etc. Among them, nickel acetate is preferred as the transition metal source. The transition metal source is preferably an aqueous solution, more preferably a nickel acetate aqueous solution.
[0234] In the present embodiment, the transition metal source may be only one kind or two or more kinds.
[0235] When using nickel acetate aqueous solution as a transition metal source, urea may be mixed to generate amine in the nickel acetate aqueous solution to provide an alkaline environment, thereby facilitating the formation of the target Ni(OH) 2 .
[0236] The mixing method is not particularly limited, but it is preferable to mix the nickel solution with the molybdenum carbide dispersion.
[0237] As the dispersion liquid of molybdenum carbide, a mixture of water and molybdenum carbide can be exemplified.
[0238] A composite of molybdenum carbide and the nickel compound may be formed by mixing a nickel compound solution with molybdenum carbide to obtain a mixture, and contacting the molybdenum carbide with the nickel compound solution.
[0239] From the viewpoint of preventing agglomeration of molybdenum carbide, for example, it is preferable to stir the mixture of the nickel compound solution and molybdenum carbide. The stirring speed can be, for example, 50 to 1000 rpm.
[0240] The concentration of nickel in the nickel compound solution may be 0.0001 to 1 mol / L, or 0.001 to 0.1 mol / L.
[0241] The temperature of the mixture may be any temperature at which the second composite can be formed, and may be, for example, 10 to 100°C, or 20 to 90°C.
[0242] The retention time of the mixture may be any time period sufficient to form the second composite, and as an example, may be 10 minutes to 48 hours, or 30 minutes to 12 hours.
[0243] In the method for producing the second composite of the embodiment, the second composite can be produced even without performing a heat treatment. For example, the obtained mixture of the second composite, the nickel compound solution and the molybdenum carbide is preferably not heated at a temperature of 200° C. or higher, more preferably not heated at a temperature of more than 100° C., and even more preferably not heated at a temperature of more than 80° C.
[0244] After the second composite is formed from the above mixture, the second composite can be separated by centrifugation, drying, or the like, thereby easily recovering the second composite according to the embodiment.
[0245] <Oxygen Generation Catalyst>
[0246] The second composite of the embodiment can be suitably used as a catalyst in the oxygen evolution reaction (OER) (sometimes referred to as an "oxygen evolution catalyst" in this specification). In addition, the second composite of the embodiment can also be used as an oxygen evolution catalyst by being used in combination with a conductive material. That is, as a preferred oxygen evolution catalyst, for example, an oxygen evolution catalyst containing the second composite of the embodiment can be cited, and the above-mentioned oxygen evolution catalyst can further contain a conductive material in addition to the second composite of the embodiment. The catalytic activity of the oxygen evolution catalyst containing the second composite of the embodiment and the conductive material in the oxygen evolution reaction (OER) becomes higher.
[0247] Examples of the conductive material include the same conductive materials as those in the oxygen generating catalyst.
[0248] The metal as the conductive material contained in the oxygen generating catalyst may be only one kind or two or more kinds.
[0249] The oxygen generating catalyst may contain carbon instead of metal, may contain metal instead of carbon, or may contain both metal and carbon as a conductive material.
[0250] In the oxygen generating catalyst, the content of the conductive material is preferably 0.1 to 50% by mass, and more preferably 0.5 to 40% by mass, relative to the content of the second composite of the embodiment.
[0251] In the oxygen generation catalyst, the total content of the second composite of the embodiment and the above-mentioned conductive material relative to the total mass (100 mass %) of the oxygen generation catalyst is preferably 80 mass % or more, more preferably 90 mass % or more, and further preferably 95 mass % or more, for example, 97 mass % or more, and any one of 99 mass % or more, or 100 mass %. By the above ratio being above the above lower limit, the catalyst activity of the oxygen generation catalyst in the oxygen generation reaction (OER) becomes higher. As long as the above ratio is 100 mass % or less.
[0252] When the oxygen generation catalyst of the embodiment is applied to a battery, the electrolyte solution is not particularly limited, and a known electrolyte solution can be used, preferably a potassium hydroxide solution.
[0253] <Third Catalyst Ink>
[0254] The second composite is suitable as a component contained in the catalyst ink.
[0255] The catalyst ink of the embodiment (hereinafter also referred to as “third catalyst ink”) contains the second composite of the embodiment and a solvent.
[0256] The third catalyst ink of the embodiment may contain the second composite of the embodiment, a polymer electrolyte, and a solvent.
[0257] The third catalyst ink of the present embodiment may further contain a conductive material. Examples of the conductive material include the conductive materials exemplified above.
[0258] The third catalyst ink can be applied to, for example, a working electrode substrate to form a catalyst layer.
[0259] Examples of the polymer electrolyte and the solvent include the same polymer electrolytes and solvents as those described above for the second catalyst ink.
[0260] Example
[0261] Hereinafter, the present invention will be described in further detail by way of Examples, but the present invention is not limited to these Examples.
[0262] (Manufacturing of molybdenum trioxide powder)
[0263] Molybdenum trioxide was produced using an RHK simulator (manufactured by Noritake Company Limited) as a calcining furnace and a VF-5N dust collector (manufactured by Amano Co., Ltd.) as a dust collector.
[0264] 1.5 kg of aluminum hydroxide (manufactured by Nippon Light Metal Co., Ltd.) and 1 kg of molybdenum trioxide (manufactured by Nippon Inorganic Co., Ltd.) were mixed, then placed in a sagger and calcined at a temperature of 1100° C. for 10 hours. During calcination, external air was introduced from the side and bottom of the calcination furnace (blowing rate: 150 L / min, external air temperature: 25° C.). Since molybdenum trioxide evaporates in the furnace, it cools near the dust collector and precipitates in the form of particles, 900 g of molybdenum trioxide 1 was obtained in the dust collector.
[0265] The median particle size D50 of the primary particles determined by dynamic light scattering was 87.8 nm, and the purity of molybdenum trioxide 1 (MoO 3 The content ratio) is 99.9 mass %.
[0266] In addition, the crystal structure of molybdenum trioxide (1) was analyzed by X-ray diffraction (XRD), and the peaks of molybdenum trioxide belonging to α crystal and β crystal were observed, and no other peaks were observed. Then, the peak intensity ratio of the (011) plane of the β crystal and the (021) plane of the α crystal was compared, and the result was that β(011) / α(021) was 4. Furthermore, the comprehensive powder X-ray analysis software PDXL2 manufactured by Rigaku Co., Ltd. was applied, LaB6 (NIST SRM660c LaB6 Standard Powder) was used as the standard material to determine the XRD device constant, and the crystallite size was evaluated using the Scherrer method. As a result, it was confirmed that molybdenum trioxide (1) has a crystal structure including α crystals with an average crystallite size of 15.7nm and β crystals with an average crystallite size of 16.8nm.
[0267] <Evaluation of molybdenum oxide powder>
[0268] [Method for measuring the average particle size of primary particles of molybdenum trioxide powder]
[0269] 0.1 g of molybdenum trioxide powder was added to 10 cc of ethanol, and after ultrasonic treatment for 4 hours in an ice bath, ethanol was appropriately adjusted to a concentration within the measurable range of a dynamic light scattering particle size distribution measuring device (Nanotrac Wave II manufactured by MicrotracBEL), and a measurement sample was obtained. Using the measurement sample, a dynamic light scattering particle size distribution measuring device (Nanotrac Wave II manufactured by MicrotracBEL) was used to measure the particle size distribution in the range of 0.0001 to 10 μm, and the median particle size D50 was calculated. Among them, for the measurement sample with a median particle size D50 exceeding 10 μm, the solution was adjusted in the same manner, and a laser diffraction particle size distribution measuring device (SALD-7000 manufactured by Shimadzu Corporation) was used to measure the particle size distribution in the range of 0.015 to 500 μm, and the median particle size D50 was calculated.
[0270] [Crystal structure analysis of molybdenum trioxide powder: XRD method]
[0271] The sample of the molybdenum compound obtained in each example was filled into a measurement sample holder with a depth of 0.5 mm, and placed in an X-ray diffraction (XRD) device (Ultima IV manufactured by Rigaku Co., Ltd., the optical system using a parallel beam method + scintillation counting detector, rotating table), and measured under the conditions of Cu / Kα rays, 40 kV / 40 mA, scanning speed (2θ) 2° / min, spacing (2θ) 0.02°, and scanning range (2θ) greater than 10° and less than 70°.
[0272] [Method for measuring crystallite size of molybdenum trioxide powder]
[0273] The XRD apparatus constants were determined using comprehensive powder X-ray analysis software PDXL2 manufactured by Rigaku Co., Ltd., using LaB6 (NIST SRM660c LaB6 Standard Powder) as a standard substance, and the crystallite size was evaluated using the Scherrer method (using the Scherrer constant K=0.94).
[0274] [Purity determination of molybdenum trioxide: XRF analysis]
[0275] Using a fluorescent X-ray analyzer Primus IV (manufactured by Rigaku Co., Ltd.), about 20 to 30 mg of the sample of the recovered molybdenum trioxide powder was taken onto filter paper and covered with a PP film for composition analysis. The amount of molybdenum obtained from the XRF analysis results was calculated by converting (mass %) to 100 mass % of molybdenum trioxide in the molybdenum trioxide powder.
[0276] (Example 1: Mo 2 Synthesis of C)
[0277] 10.5g of molybdenum trioxide, 0.17g of Ketjen black (EC300J manufactured by Lion Specialty Chemicals Co., Ltd.), 0.33g of sodium chloride, and 0.33g of potassium chloride were mixed in a mortar for 1 minute and placed in a crucible. The mixture was calcined at 850°C for 3 hours under a nitrogen atmosphere. After natural cooling, the calcined product was washed with ion exchange water to remove salts. According to XRD measurement, it can be confirmed that the obtained molybdenum carbide shows molybdenum carbide (Mo 2 C) α crystal structure.
[0278] (Examples 2-3: Mo 2 Synthesis of C)
[0279] Molybdenum carbide was synthesized in the same manner as in Example 1 except that the raw materials shown in Table 1 were used.
[0280] (Comparative Example 1)
[0281] Commercially available molybdenum carbide (manufactured by Kojundo Chemical Laboratory Co., Ltd.) was evaluated in the same manner as the molybdenum carbide of Examples 1 to 3. The results are shown in Table 2.
[0282] (Comparative Example 2)
[0283] Ketjen black (EC300J manufactured by Lion Specialty Chemicals Co., Ltd.) was evaluated in the same manner as the molybdenum carbide of Examples 1 to 3. Table 2 shows the results.
[0284] (Comparative Example 3)
[0285] 203.9 g of Ketjen black (EC300J manufactured by Lion Specialty Chemicals Co., Ltd.) and 33.6 g of molybdenum carbide (manufactured by Kojundo Chemical Laboratory Co., Ltd.) were mixed in a mortar. The obtained mixture was evaluated in the same manner as the molybdenum carbide in Examples 1 to 3. The results are shown in Table 2.
[0286] [Table 1]
[0287]
[0288] In Table 1, “MoO 3 "(1)" represents molybdenum trioxide 1, and "KB" represents Ketjen black (EC300J manufactured by Lion Specialty Chemicals Co., Ltd.).
[0289] <Evaluation>
[0290] The molybdenum carbides of Examples 1 to 3, the commercially available molybdenum carbide of Comparative Example 1, the Ketjen black of Comparative Example 2, and the mixture of Comparative Example 3 were evaluated as follows.
[0291] [Elemental analysis]
[0292] The molybdenum content was determined by heated closed acid decomposition-ICP-AES (inductively coupled plasma atomic emission spectrometry). More specifically, the sample was dissolved in a mixed acid of sulfuric acid and nitric acid at 180° C. for 12 hours or more, and the measurement was performed under the following conditions.
[0293] ICP emission spectrometry (device: Thermo Fisher Scientific. iCAP 6300DUO), PF power: 1150 W,
[0294] Flow rate: 52rpm,
[0295] Auxiliary gas: 0.5L / min,
[0296] Nebulizer gas: 0.6L / min,
[0297] Plasma view: axial.
[0298] The carbon content was determined by CHN elemental analysis (MICROCORDER JM10, manufactured by J-SCIENCE LAB).
[0299] [Specific surface area measurement: BET method]
[0300] The molybdenum carbide sample was measured using a specific surface area meter (BELSORP-mini, manufactured by Microtrac BEL) and the surface area per 1 g of the sample was calculated from the amount of nitrogen adsorbed using the BET method and was taken as the specific surface area (m 2 The result is taken as “BET specific surface area (m 2 The content of α-hydroxy-1-nitropropene (β-hydroxy-1-nitropropene) is shown in Table 2.
[0301] [Crystal structure analysis: XRD method]
[0302] The sample of molybdenum carbide obtained in each embodiment was filled to a depth of 0.5 mm with a sample holder, and was set in an X-ray diffraction (XRD) device (Ultima IV manufactured by Rigaku Co., Ltd.), and measured under the conditions of Cu / Kα ray, 40kV / 40mA, scanning speed (2θ) 2° / min, and scanning range (2θ) 10° or more and 70° or less. The results are shown in Table 2 as "Crystalline Size (nm)".
[0303] [Median particle size D 50 Determination method of
[0304] 0.1 g of the sample powder was added to 20 cc of acetone, and ultrasonic treatment was performed in an ice bath for 4 hours. Then, the concentration was appropriately adjusted to a measurable range of a dynamic light scattering particle size distribution measuring device (manufactured by Microtrac BEL, Nanotrac Wave II) using acetone to obtain a measurement sample. The measurement sample was used to measure the particle size distribution in the range of 0.0001 μm to 10 μm using a dynamic light scattering particle size distribution measuring device, and the particle size at which the volume cumulative % ratio becomes 50%, i.e., the median particle size D was calculated. 50 .
[0305] The result is "D 50 (nm)” are shown in Table 2.
[0306] [Analysis using Raman spectroscopy]
[0307] The powder sample was placed on a glass slide and measured using a laser Raman spectrophotometer (manufactured by JASCO Corporation, NRS-5500) under the conditions of excitation laser 532nm, laser intensity 0.6mW, exposure time 30sec, and point measurement with an objective lens magnification of 100 times. After the measurement, the baseline-corrected spectrum XPS was analyzed using the analysis software Spectra Manager. The results are shown in Table 2 as "G / D(au)".
[0308] [Measurement method of volume resistivity]
[0309] About 0.5 g of sample powder was placed in a measuring jig, and the resistance was measured by an automatic powder resistance measuring system (Made by Nittoseiko Analytech, MCP-PD600) at a load of 4 to 20 kN, and the volume resistivity was calculated from the volume of the powder. The results are shown in Table 2 as "Volume resistivity @ 64 MPa".
[0310] Table 2 shows the above measurement results.
[0311] [Table 2]
[0312]
[0313] The results of XRD analysis are shown in Figure 2 .like Figure 2 As shown, it can be confirmed that the molybdenum carbides obtained in Examples 1 to 3 all show molybdenum carbide (Mo 2 C). In addition, it was confirmed that the molybdenum carbide (Mo 2 C) The crystal structure is α crystal.
[0314] Figure 3 Observation images of each particle of Examples 1 to 3 obtained by transmission electron microscopy (TEM, manufactured by JEOL Ltd., JEM-1400) are shown. Figure 3 As shown, it was confirmed that the molybdenum carbides of Examples 1 to 3 all had a sheet structure.
[0315] Figure 4 The observation image of the particles of Example 1 obtained by high-resolution transmission electron microscopy (HRTEM, manufactured by JEOL Ltd., JEM-ARM300F) is shown. Since Mo and C overlap according to the EDS mapping image, and Mo can be seen according to the high-resolution TEM 2 C lattice image, it can be confirmed that the compound of Example 1 is Mo 2 C is the main phase. In addition, an oxide film (MoO 3 ).
[0316] [Preparation of catalyst ink and evaluation of hydrogen generation activity (1)]
[0317] 4 mg of any one of the molybdenum carbides of Examples 1 to 3, the commercially available molybdenum carbide of Comparative Example 1, the Ketjen black of Comparative Example 2, and the mixture of Comparative Example 3, 2 mg of Ketjen black, and 40 ul of a 5% Nafion dispersion (Nafion dispersion solution of Fujifilm Wako Pure Chemical Industries, Ltd.) were ultrasonically dispersed in 1 ml of ethanol for 1 hour to prepare an ink. 20 ul of the obtained ink dispersion was applied to the surface of the electrode. After the surface liquid dried naturally, the electrode was moved to a vacuum dryer and dried at 60°C for more than 6 hours. The hydrogen generation activity of the prepared electrode was evaluated by a three-electrode system. The evaluation conditions were to use the LSV method with a scanning voltage range of -0.3 V to 0 V and a scanning speed of 5 mV / S. At a current density of 10 mA / cm 2 Overvoltage (mV), current density (mA / cm 2 ) are shown in Table 3.
[0318] [Table 3]
[0319] Overvoltage(mV) <![CDATA[Current density (mA / cm 2 )]]> Example 1 249 28.6 Example 2 284 14.6 Example 3 Unable to determine 0.7 Comparative Example 1 234 33.9 Comparative Example 2 Unable to determine 1.2 Comparative Example 3 256 22.1
[0320] (Example 4: Synthesis of Palladium-Molybdenum Carbide Composite 1)
[0321] 100 mg of molybdenum carbide of Example 2 was dissolved in methanol (reagent from Kanto Chemical Co., Ltd., CH 3 OH) was dispersed by ultrasonic for 30 minutes to obtain a dispersion. Palladium acetate (reagent from Kanto Chemical Co., Ltd., Pd(CH 3 COO 2) 42.2 mg was dissolved in methanol, and the obtained solution was added to the above dispersion while stirring. Then, it was irradiated with light and stirred at room temperature for more than 2 hours. The precipitate in the dispersion was recovered by a centrifuge, ultrasonically cleaned with water 3 times and dried in a vacuum, thereby obtaining a Pd-modified molybdenum carbide powder (palladium-molybdenum carbide composite 1).
[0322] (Examples 5-6: Synthesis of Palladium-Molybdenum Carbide Composite 2 and Palladium-Molybdenum Carbide Composite 3)
[0323] Palladium-platinum carbide composite 2 and palladium-platinum carbide composite 3 were synthesized in the same manner as in Example 4 except that the raw materials shown in Table 4 were used.
[0324] (Comparative Example 1)
[0325] Commercially available molybdenum carbide (manufactured by Kojundo Chemical Laboratory Co., Ltd.) was evaluated in the same manner as in the palladium-molybdenum carbide composites 1 to 3 of Examples 4 to 6. The results are shown in Table 5.
[0326] (Comparative Example 4)
[0327] Palladium-modified Ketjen black (4% Pd-KB) was synthesized in the same manner as in Example 4 except that the raw materials shown in Table 4 were used.
[0328] [Table 4]
[0329]
[0330] In Table 4, “Mo 2 C-4" represents molybdenum carbide of Example 1, "Mo 2 "C-6" represents the molybdenum carbide of Example 2, and "KB" represents Ketjen black (EC300J manufactured by Lion Specialty Chemicals Co., Ltd.).
[0331] <Evaluation>
[0332] The palladium-molybdenum carbide composites 1 to 3 of Examples 4 to 6, the commercially available molybdenum carbide of Comparative Example 4, and the 4% Pd-KB of Comparative Example 5 were evaluated as follows.
[0333] [XRF analysis]
[0334] Using a fluorescent X-ray analyzer Primus IV (manufactured by Rigaku), about 20 to 30 mg of the sample was taken onto filter paper and covered with a PP film for composition analysis. The amount of palladium obtained from the XRF analysis results was obtained as the amount of palladium (mass %) relative to 100% by mass of the sample particles. The results are shown in Table 5 as "Pd (wt %)".
[0335] [Crystal structure analysis: XRD method]
[0336] The measurement was performed in the same manner as in Examples 1 to 3 and Comparative Examples 1 to 3. The results are shown in Table 5 as "Crystalline Size (nm)".
[0337] [Median particle size D 50 Determination method of
[0338] The measurement was carried out in the same manner as in Examples 1 to 3 and Comparative Examples 1 to 3. The results are referred to as "D 50 (nm)” are shown in Table 5.
[0339] [Analysis using Raman spectroscopy]
[0340] The measurement was performed in the same manner as in Examples 1 to 3 and Comparative Examples 1 to 3. The results are shown in Table 5 as "G / D (au)".
[0341] [Specific surface area measurement: BET method]
[0342] The specific surface area (m 2 The result is taken as “BET specific surface area (m 2 The content of α-hydroxy-1-nitropropene (β-hydroxy-1-nitropropene) is shown in Table
[0343] [Table 5]
[0344]
[0345] The results of XRD analysis are shown in Figure 5 .in addition, Figure 6 Observation images of each particle of Examples 4 to 6 obtained by a transmission electron microscope (TEM, manufactured by JEOL Ltd., JEM-1400) are shown. Figure 5 and Figure 6 From the results shown, it was confirmed that the compounds obtained in Examples 4 to 6 were all Pd-molybdenum carbide composites.
[0346] Figure 7 The following is an observation image of the particles of Example 4 obtained by a high-resolution transmission electron microscope (HRTEM, manufactured by JEOL Ltd., JEM-ARM300F). From the EDS mapping image, it is believed that the white spherical particles correspond to Pd particles.
[0347] Figure 8 This is a HAADF-STEM image of the particles of Example 4 (transmission electron image, manufactured by JEOL Ltd., JEM-ARM300F). Fig. 9This is a SEI image of the particles of Example 4 (secondary electron image, manufactured by JEOL Ltd., JEM-ARM300F). Figure 8 and Fig. 9 In the figure, the same type of arrows represent the same Pd particles.
[0348] according to Figure 8 and Fig. 9 The results shown confirm that a large number of Pd nanoparticles with a maximum size of about 20 nm exist on the outermost surface of molybdenum carbide.
[0349] [Preparation of catalyst ink and evaluation of hydrogen generation activity (2)]
[0350] 4 mg of any one of the palladium-molybdenum carbide composites 1 to 3 of Examples 4 to 6, the commercially available molybdenum carbide of Comparative Example 4, and the 4% Pd-KB of Comparative Example 5, 2 mg of Ketjen Black, and 40 ul of 5% Nafion dispersion (Nafion dispersion solution of Fujifilm Wako Pure Chemical Industries, Ltd.) were ultrasonically dispersed in 1 ml of ethanol for 1 hour to prepare ink. 20 ul of the obtained ink dispersion was applied to the surface of the electrode. After the surface liquid dried naturally, the electrode was moved to a vacuum dryer and dried at 60°C for more than 6 hours. The hydrogen generation activity of the prepared electrode was evaluated by a three-electrode method. The evaluation conditions were as follows: using the LSV method, with a scanning voltage range of -0.3 V to 0 V and a scanning speed of 5 mV / S. At a current density of 10 mA / cm 2 Overvoltage (mV), current density (mA / cm 2 ) are shown in Table 6.
[0351] [Table 6]
[0352] (Example 7: Synthesis of Nickel Hydroxide-Molybdenum Carbide Composite 1)
[0353] 100 mg of molybdenum carbide of Example 2 was dispersed in 40 ml of pure water by ultrasonication for 30 minutes to obtain a dispersion. 198.7 mg of nickel (II) acetate tetrahydrate (Kanto Chemical Co., Ltd., Ni(CH 3 COO 2 ·4H 2 O), urea 320 mg (Kanto Chemical Co., Ltd., NH 2 CONH 2 ) was dissolved in 40 ml of pure water to obtain a solution. The above dispersion was added to the above solution while stirring, and kept at 85°C for 3 hours. The precipitate in the dispersion was recovered by a centrifuge, ultrasonically cleaned 3 times with water and dried in a vacuum, thereby obtaining Ni(OH) 2Powder of modified molybdenum carbide (nickel hydroxide-molybdenum carbide composite 1).
[0354] (Comparative Example 6)
[0355] Commercially available molybdenum carbide (manufactured by Kojundo Chemical Research Institute Co., Ltd.) was prepared by mixing with Ni(OH) 2 -Molybdenum carbide composite 1 was evaluated in the same manner. The results are shown in Table 8.
[0356] [Table 7]
[0357]
[0358] In Table 7, “Mo 2 C-6" represents the molybdenum carbide of Example 2.
[0359] <Evaluation>
[0360] The nickel hydroxide-molybdenum carbide composite 1 of Example 7 and the commercially available molybdenum carbide of Comparative Example 8 were evaluated as follows.
[0361] [XRF analysis]
[0362] Using a fluorescent X-ray analyzer Primus IV (manufactured by Rigaku Co., Ltd.), about 20 to 30 mg of the sample was taken onto filter paper and covered with a PP film for composition analysis. The palladium content (mass %) in the composite relative to 100 mass % of the sample particles was calculated by adding the palladium amount, molybdenum amount, and molybdenum carbide composition (shown in Table 2) obtained from the XRF analysis results.
[0363] [Crystal structure analysis: XRD method]
[0364] The measurement was performed in the same manner as in Examples 1 to 3 and Comparative Examples 1 to 3. The results are shown in Table 8 as "Crystalline Size (nm)".
[0365] [Median particle size D 50 Determination method of
[0366] The measurement was carried out in the same manner as in Examples 1 to 3 and Comparative Examples 1 to 3. The results are referred to as "D 50 (nm)” are shown in Table 8.
[0367] [Analysis using Raman spectroscopy]
[0368] The measurement was performed in the same manner as in Examples 1 to 3 and Comparative Examples 1 to 3. The results are shown in Table 8 as "G / D (au)".
[0369] [Specific surface area measurement: BET method]
[0370] The specific surface area (m 2 The result is taken as “BET specific surface area (m 2 / g)" is shown in Table 8.
[0371] [Table 8]
[0372]
[0373] The results of XRD analysis are shown in Fig.10 . Fig.11 FIG. 8 shows an observation image of the particles of Example 7 obtained by a transmission electron microscope (TEM). Fig.11 The results shown can be confirmed with Figure 3 Compared with the TEM image of molybdenum carbide, Ni(OH) is generated on the surface of molybdenum carbide. 2 Nanosheets.
[0374] [Preparation of catalyst ink and evaluation of oxygen generation activity]
[0375] The nickel hydroxide-molybdenum carbide composite 1 of Example 7, 4 mg of any one of the commercially available molybdenum carbides of Comparative Example 8, 2 mg of Ketjen Black, and 40 ul of a 5% Nafion dispersion (Nafion dispersion solution of Fujifilm Wako Pure Chemical Industries, Ltd.) were ultrasonically dispersed in 1 ml of ethanol for 1 hour to prepare an ink. 20 ul of the obtained ink dispersion was applied to the surface of the electrode. After the surface liquid dried naturally, the electrode was moved to a vacuum dryer and dried at 60°C for more than 6 hours. The hydrogen generation activity of the prepared electrode was evaluated by a three-electrode system. The electrolyte was a 1.0 mol / L potassium hydroxide solution (Kanto Chemical Co., Ltd., Potassium hydroxide solution). The evaluation conditions were performed using the LSV method with a scanning voltage range of 1.0 V to 1.8 V and a scanning speed of 5 mV / S. The current density was 10 mA / cm 2 Overvoltage (mV), current density at voltage 1.8V (mA / cm 2 ) are shown in Table 9.
[0376] [Table 9]
[0377] Each configuration and combination thereof in each embodiment is an example, and addition, omission, substitution and other changes of configurations can be made without departing from the gist of the present invention. In addition, the present invention is not limited to each embodiment but only to the scope of claims.
Claims
1. A molybdenum carbide having a Mo2C crystal structure and a carbon content of 6% or more relative to the total mass of the molybdenum carbide, i.e. 100% by mass.
2. The molybdenum carbide according to claim 1, wherein Graphite ribbons G and diamond ribbons D derived from carbon were present as determined by Raman spectroscopy.
3. The molybdenum carbide according to claim 2, wherein: The ratio of the carbon-derived graphite ribbon G to the diamond ribbon D, that is, G / D, is 0.75 or more.
4. The molybdenum carbide according to claim 1, wherein The specific surface area measured by the BET method is 10 to 2000 m 2 / g.
5. The molybdenum carbide according to claim 1, wherein The median particle size D was calculated by dynamic light scattering. 50 Below 1000nm.
6. The molybdenum carbide according to claim 1, wherein The average crystallite size determined from the peak at 2θ=39.4±0.5° in a pattern obtained by X-ray diffraction measurement was 50 nm or less.
7. A catalyst ink comprising the molybdenum carbide according to claim 1 and a solvent. 8 . A composite material comprising noble metal particles having an average particle size of 20 nm or less and the molybdenum carbide according to claim 1 .
9. The composite according to claim 8, wherein The noble metal particles are palladium particles.
10. The composite according to claim 9, wherein The palladium particles include an aggregate of palladium atoms having no crystal structure.
11. A catalyst ink comprising the composite according to claim 8 and a solvent. 12 . A composite material comprising at least one transition metal species selected from the group consisting of transition metals and transition metal compounds and the molybdenum carbide according to claim 1 .
13. The composite with molybdenum carbide according to claim 12, wherein The transition metal species is at least one selected from the group consisting of nickel and nickel compounds.
14. A catalyst ink comprising the composite according to claim 12 and a solvent.
15. A method for producing molybdenum carbide, comprising: Molybdenum trioxide including α crystals having an average crystallite size of 50 nm or less, and carbon are calcined in the presence of at least one inorganic compound selected from the group consisting of inorganic salts and inorganic hydroxides.
16. The method for producing molybdenum carbide according to claim 15, wherein: The inorganic compound is at least one selected from the group consisting of sodium compounds and potassium compounds.
17. A method for producing a composite, comprising the steps of mixing molybdenum carbide with a noble metal solution, The molybdenum carbide has a Mo2C crystal structure, and the carbon content is 6% or more relative to the total mass of the molybdenum carbide, that is, 100% by mass.
18. A method for producing a composite, comprising the steps of mixing molybdenum carbide with a transition metal compound solution, The molybdenum carbide has a Mo2C crystal structure, and the carbon content is 6% or more relative to the total mass of the molybdenum carbide, that is, 100% by mass.
Citation Information
Patent Citations
Production of carbide of heavy metals having a high specific surface area
JP1991501721A
Hydrogen generating electrode
JP2001234380A
Game machine
JP2022125418A
